ΔFosB Mediates Epigenetic Desensitization of the c-fos Gene After Chronic Amphetamine Exposure - Renthal, William (Society for Neuroscience, 2008)
The molecular mechanisms underlying the transition from recreational drug use to chronic addiction remain poorly understood. One molecule implicated in this process is ΔFosB, a transcription factor that accumulates in striatum after repeated drug exposure and mediates sensitized behavioral responses to psychostimulants and other drugs of abuse. The downstream transcriptional mechanisms by which ΔFosB regulates drug-induced behaviors are incompletely understood. We reported previously the chromatin remodeling mechanisms by which ΔFosB activates the expression of certain genes; however, the mechanisms underlying ΔFosB-mediated gene repression remain unknown. Here, we identify c-fos, an immediate early gene rapidly induced in striatum after acute psychostimulant exposure, as a novel downstream target that is repressed chronically by ΔFosB. We show that accumulation of ΔFosB in striatum after chronic amphetamine treatment desensitizes c-fos mRNA induction to a subsequent drug dose. ΔFosB desensitizes c-fos expression by recruiting histone deacetylase 1 (HDAC1) to the c-fos gene promoter, which, in turn, deacetylates surrounding histones and attenuates gene activity. Accordingly, local knock-out of HDAC1 in striatum abolishes amphetamine-induced desensitization of the c-fos gene. In concert, chronic amphetamine increases histone H3 methylation on the c-fos promoter, a chromatin modification also known to repress gene activity, as well as expression levels of the H3 histone methyltransferase, KMT1A (lysine methyltransferase 1A, formerly SUV39H1). This study reveals a novel epigenetic pathway through which ΔFosB mediates distinct transcriptional programs that may ultimately alter behavioral plasticity to chronic amphetamine exposure.